Analisis Pengembangan Integrasi Ilmu Agama Buddha Dan Umum Di Sekolah Tinggi Agama Buddha Negeri (STABN) Sriwijaya - Sulaiman Sulaiman (Jurnal Ilmiah Kampus: Sati Sampajanna, 2020)
The study in this paper suggests the development of integration between Buddhism and general science at the Sriwijaya State Buddhist College (STABN). Conceptualized of belief (Pali: saddhā, Sanskrit: śraddhā) in Buddhism as a scientific spirit built on the Ehipassiko doctrine. Similar to the science of belief that a Buddhist cultivates must be explored and proven to provide enlightenment in human life. This study uses a qualitative method of documentation study in collecting data and processing it. The results of this study indicate that educators have not yet maximally studied as a driving force for scientific development at this institution. This is indicated by the absence of reputable scientific works; training, and the socialization of clear scientific integration in the Buddhist general-religious study program to the teaching staff. It is hoped that this study will provide input to an in-depth study of the integration of general science and Buddhism, especially in the aspects of the curriculum that was developed to produce graduates following the motto of STABN Sriwijaya Excellence, Buddhistic and Character.